Nominal rigidities in debt and product markets - Carlos Garriga; Finn E. Kydland; Roman Šustek (Queen Mary University of London, School of Economics and Finance, 2016)
Standard models used for monetary policy analysis rely on sticky prices. Recently, the literature started to explore also nominal debt contracts. Focusing on mortgages, this paper compares the two channels of transmission within a common framework. The sticky price channel is dominant when shocks to the policy interest rate are temporary, the mortgage channel is important when the shocks are persistent. The first channel has significant aggregate effects but small redistributive effects. The opposite holds for the second channel. Using yield curve data decomposed into temporary and persistent components, the redistributive and aggregate consequences are found to be quantitatively comparable.
Keywords: E32; E52; G21; R21; 330; Mortgage contracts; Sticky prices; Monetary policy; Yield curve; Redistributive vs. aggregate effects